Income inequality and the definition of income : the case of Malaysia - Kusnic, Michael W., 1952-; DaVanzo, Julie S.; Rand eBooks (Santa Monica, CA : RAND, 1980)
Explores the sensitivity of estimates of Malaysian income levels, interethnic or urban/rural differences, and income inequality to several factors. Using four measures of income, the report shows that estimates of income inequality in Malaysia or among its ethnic subgroups are very sensitive to how broadly income is defined and to the other factors examined. For example, failure to consider nonmarket sources of income leads to serious underestimates of the relative income share of the poorest quintile of the population; that share more than doubles when the definition of income is broadened from market income to measures that include the value of nonmarket production, such as cottage industry. Such startling disparities should warn researchers and policymakers to be extremely careful in processing and interpreting income data, especially when comparing data from different studies, countries, or periods.
"June 1980."
Includes bibliographical references (p. 119-121).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Income distribution -- Malaysia; Electronic books